Does belonging accompany believing? Correlations and trends in Western Europe and North America between 1981 and 2000 - Aarts, O; Need, A; Te Grotenhuis, M; De Graaf, N (Springer, 2008)
Using the European and World Value Surveys from 1981, 1990, and 2000, this paper examines trends in Christian beliefs, church attendance, and the relationship between believing and belonging. It further looks at the influence of religious pluralism on this relationship in Western Europe and North America. The main finding of this study is that in most countries there is no growing gap between Christian believing and Christian belonging. Indeed, the relationship between believing and belonging at the individual level has remained practically unchanged in the Western world over the past two decades. The slight weakening in the relation between believing and belonging measured for some countries stems from the fact that in those countries both believing and belonging declined, but the decline in belonging was stronger. Moreover, a higher degree of religious pluralism does not result in a stronger association between believing and belonging, as would be expected from supply-side theory.